A method for producing micro-segment green sand for ultrafine grinding

By using the mixing method of bentonite, coal powder and old sand in the microsphere micro-section molded sand production, combined with vibration compaction and natural drying processes, the problems of high costs and pollution in traditional methods are solved, and product quality and production efficiency are improved.

CN119772101AInactive Publication Date: 2025-04-08NINGGUO DONGFANG MILLING MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411644315.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The traditional coated sand shell production method uses expensive chemical reagents, which increases production costs, and is difficult to ensure the dimensional accuracy of the cavity, affects product quality, and is difficult to handle waste, which easily causes secondary pollution.

Method used

The production method of micro-ball micro-section mould sand for ultrafine grinding is adopted. By mixing bentonite, coal powder and old sand in a certain proportion, adding appropriate amount of water to stir, pouring it into the mold and compacting it by vibration, drying it naturally or drying at low temperature, to make a mould sand model.

Benefits of technology

It improves the adhesion and fire resistance of the damp mold sand, reduces production costs and environmental pollution, ensures the dimensional accuracy and surface quality of the cavity, realizes the recycling and utilization of resources, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119772101A_ABST
    Figure CN119772101A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of microsphere micro-segment wet sand production, and discloses a method for producing microsphere micro-segment wet sand for ultrafine grinding, wherein the production steps include mixing bentonite, coal powder and old sand in a certain proportion; adding an appropriate amount of water to the mixture, stirring and mixing for 10 minutes; pouring the mixed wet sand into a mold, and compacting it by vibration. The method for producing microsphere micro-segment wet sand for ultrafine grinding ensures the quality and purity of raw materials by selecting high-quality bentonite and coal powder with moderate fineness, as well as screened and cleaned old sand. The high-quality raw material combination not only improves the cohesion and fire resistance of the wet sand, but also reduces the interference of impurities in the production process. By accurately calculating and adding an appropriate amount of water, the wetness of the wet sand is ensured to be moderate, and the dry block and agglomeration phenomenon caused by excessive or insufficient water is avoided. By selecting a suitable mold and performing surface treatment, the dimensional accuracy and surface quality of the cavity are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of microsphere micro-segment green sand production, in particular to a method for producing microsphere micro-segment green sand for ultrafine grinding. Background Art

[0002] The production of microsphere and micro-segment green sand refers to the method of using green sand to make molds in the production process of microsphere and micro-segment for ultrafine grinding. However, most of the traditional coated sand shell mold production methods use chemical reagents such as resins and hexamethylenetetramine. These materials are expensive, which increases production costs. In addition, the waste generated by the traditional method is difficult to handle and easily causes secondary pollution. At the same time, the traditional method is difficult to ensure the dimensional accuracy of the cavity, which affects the quality of the final product. The recycling rate of old sand is low, resulting in waste of resources. Summary of the invention

[0003] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0004] To achieve the above object, the present invention provides the following technical solutions:

[0005] A method for producing micro-segment green sand for ultrafine grinding, the production steps comprising:

[0006] Mix bentonite, coal powder and old sand in a certain proportion;

[0007] Add appropriate amount of water to the mixture and stir for 10 minutes;

[0008] Pour the mixed green sand into the mold and compact it by vibration to form a cavity of the desired shape;

[0009] Adjust the vibration table according to the vibration parameter threshold;

[0010] The prepared cavity is naturally dried or low-temperature dried to obtain the final green sand mold.

[0011] As a further solution of the present invention: the mixing of bentonite, coal powder and old sand in a certain proportion includes:

[0012] Select high-quality bentonite and coal powder with moderate fineness as reducing agent and fuel. At the same time, the selected old sand needs to be screened and cleaned to remove impurities and dust;

[0013] The preparation ratio of bentonite, coal powder and old sand is 1:1:8;

[0014] Weigh bentonite, coal powder and old sand according to the above proportions, put them into a mixer, start the mixer and carry out preliminary mixing.

[0015] As a further embodiment of the present invention: the step of adding an appropriate amount of water to the mixture and stirring and mixing for 10 minutes comprises:

[0016] The amount of water added is 5% to 10% of the total weight of the mixture, and the expression is as follows:

[0017]

[0018] Where W is the amount of water added, in kg, P is the percentage of water, ranging from 5% to 10%, and M is the total weight of the mixture, in kg;

[0019] Spray the calculated water evenly into the mixture, then turn on the mixer and stir and mix for 10 minutes;

[0020] During the mixing process, make sure the mixture is fully moistened and free of dry lumps and lumps.

[0021] As a further solution of the present invention: the mixed green sand is poured into the mold and compacted by vibration to form a cavity of a desired shape, comprising:

[0022] Choose a mold of appropriate size and shape, ensure that the inner surface of the mold is smooth, free of burrs and cracks, and treat the inner surface of the mold with a release agent;

[0023] Pour the mixed green sand evenly into the mold;

[0024] During the filling process, vibrate the mold appropriately to allow the green sand to be filled into the mold more tightly;

[0025] Place the mold filled with green sand on a vibration table and start the vibration table for vibration compaction.

[0026] As a further solution of the present invention: the vibration frequency and amplitude need to be optimized during the vibration compaction process, and the expression is as follows:

[0027]

[0028] Where v is the vibration frequency in Hz, A is the vibration amplitude in mm, t is the vibration time in seconds, indicating the duration of the vibration, and k is the material constant in N·s 2 / mm 3 .

[0029] As a further solution of the present invention: the adjustment of the vibration table according to the magnitude of the vibration parameter threshold includes:

[0030] When the value of f(v,A,t) is between L1 and L2, it means that the vibration parameters are set reasonably;

[0031] When the value of f(v,A,t) is less than L1, it means that the vibration parameters are too weak, the compaction effect of green sand is poor, and there may be voids and bubbles. At this time, the vibration frequency v or vibration amplitude A should be increased, or the vibration time t should be extended;

[0032] When the value of f(v,A,t) is greater than L2, it means that the vibration parameters are too strong, which may cause excessive compaction of the green sand and affect the dimensional accuracy and surface quality of the cavity. At this time, the vibration frequency v or vibration amplitude A should be reduced, or the vibration time t should be shortened.

[0033] As a further solution of the present invention: the step of naturally drying or low-temperature drying the prepared cavity to obtain the final green sand mold includes:

[0034] Place the finished cavity in a well-ventilated environment to dry naturally for 24 hours;

[0035] Or put the prepared cavity into an oven, set the temperature to 100°C to 150°C, and dry it for 2 to 4 hours.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] The quality and purity of the raw materials are ensured by selecting high-quality bentonite, coal powder with moderate fineness, and old sand that has been screened and cleaned. The high-quality raw material combination not only improves the adhesion and fire resistance of the green sand, but also reduces the interference of impurities in the production process. The wetness of the green sand is ensured to be moderate by accurately calculating and adding an appropriate amount of water, avoiding dry blocks and agglomeration caused by excessive or insufficient moisture. The dimensional accuracy and surface quality of the cavity are ensured by selecting a suitable mold and performing surface treatment. The green sand is evenly poured in and the mold is vibrated appropriately so that the green sand is evenly distributed in the mold, avoiding the generation of voids and bubbles. The efficiency and accuracy of the vibration compaction process are ensured by optimizing the vibration parameters. Reasonable vibration parameter settings enable the green sand to achieve the best compaction effect, avoiding the problem of insufficient or excessive compaction caused by improper vibration parameters. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The present invention is a schematic diagram of the process flow of a method for producing micro-sphere micro-segment green sand for ultrafine grinding. DETAILED DESCRIPTION

[0039] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the specific implementation modes of the present invention are described in detail below in conjunction with the accompanying drawings.

[0040] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0041] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.

[0042] Example

[0043] See also Figure 1 , is an embodiment of the present invention, which provides a method for producing micro-segment green sand for ultrafine grinding, verifies the effectiveness and superiority of a method for producing micro-segment green sand for ultrafine grinding, and specifically includes:

[0044] Raw material preparation: Choose high-quality bentonite, which has good adhesion and plasticity, and can improve the strength and stability of green sand. Choose coal powder with moderate fineness as a reducing agent and fuel, which helps to improve the fire resistance and air permeability of green sand. Recycle old sand to reduce costs and waste of resources. The old sand needs to be screened and cleaned to remove impurities and dust to ensure quality.

[0045] Raw material ratio: Weigh bentonite, coal powder and old sand in a ratio of 1:1:8. Specifically, if you need to prepare 100kg of green sand, you will need 10kg of bentonite, 10kg of coal powder and 80kg of old sand.

[0046] Mixing process: Put bentonite, coal powder and old sand into the mixer, turn on the mixer, and carry out preliminary mixing to ensure that the components are evenly distributed.

[0047] Add water and mix: calculate the amount of water to be added, which should be 5% to 10% of the total weight of the mixture. Assuming the total weight of the mixture is 100kg, add 5kg to 10kg of water. Spray the calculated water evenly into the mixture, then turn on the mixer and stir for 10 minutes. During the stirring process, ensure that the mixture is fully moistened without dry lumps or agglomerations.

[0048] Mould preparation: Select a mould of suitable size and shape, and ensure that the inner surface of the mould is smooth without burrs and cracks; use a release agent to treat the inner surface of the mould to prevent green sand from adhering to the mould and facilitate demoulding.

[0049] Green sand filling: Pour the mixed green sand evenly into the mold, making sure that the green sand fills every corner of the mold to avoid voids and bubbles. During the filling process, vibrate the mold appropriately to allow the green sand to be filled more tightly into the mold.

[0050] Vibration compaction: Place the mold with green sand on a vibration table, start the vibration table, and make the green sand more compact through vibration; the selection of vibration frequency and amplitude is a key factor, which directly affects the density and surface quality of the cavity; in order to optimize this process, the following formula is used to determine the best vibration parameters:

[0051]

[0052] Where v is the vibration frequency in Hz, A is the vibration amplitude in mm, t is the vibration time in seconds, indicating the duration of the vibration, and k is the material constant in N·s 2 / mm 3 .

[0053] The material constant k is measured by experiment = 0.02N·s 2 / mm 3 , the goal is to make the value of f(v,A,t) between 0.5 and 1.0, and select the vibration frequency v = 75 Hz, the vibration amplitude A = 3 mm, and the vibration time t = 1200 seconds (20 minutes).

[0054] Drying treatment: Place the finished cavity in a well-ventilated environment to dry naturally for 24 hours, or put it in an oven with the set temperature at 100℃~150℃ and the drying time for 2~4 hours.

[0055] Table: Comparison of experimental data

[0056]

[0057]

[0058] Table data analysis: Through the comparison of the above experimental data, it can be clearly seen that the green sand production method of the present invention has significant advantages and innovations over the traditional coated sand shell production method.

[0059] Cavity density: The cavity density of the traditional coated sand shell mold is 1.65g / cm 3 , while the green sand cavity density of the present invention is 1.82 g / cm 3 , higher density means that the cavity has higher structural strength and is more wear-resistant, making it suitable for high-load production environments.

[0060] Cavity surface quality: The cavity surface quality score of the traditional coated sand shell mold is 7 points, while the green sand cavity surface quality score of the present invention is 9.1 points. Higher surface quality means that the surface of the cavity is smoother, reducing the need for subsequent processing and improving production efficiency and product quality.

[0061] Vibration parameter optimization: The present invention ensures the best compaction effect of green sand by optimizing vibration parameters, using higher vibration frequency (73 Hz), larger vibration amplitude (3.1 mm) and longer vibration time (1180 s), while the traditional method has weak vibration parameters, resulting in poor compaction effect and possible presence of voids and bubbles.

[0062] Low-temperature drying time: The low-temperature drying time of the traditional coated sand shell mold is 3 hours, while the low-temperature drying time of the green sand mold of the present invention is 2.5 hours. The shorter drying time not only improves the production efficiency, but also reduces the energy consumption, further reducing the production cost.

[0063] In summary, the green sand production method of the present invention shows significant advantages in terms of cavity density, surface quality, production cost, environmental pollution level, vibration parameter optimization and low-temperature drying time. By optimizing vibration parameters and adjusting production processes, the present invention not only improves production efficiency and product quality, but also achieves green and environmentally friendly production goals. The data and analysis results provide strong support for the promotion and application of the present invention.

Claims

1. A method for producing micro-segment green sand for ultrafine grinding, characterized in that: The production steps include, Mix bentonite, coal powder and old sand in a certain proportion; Add appropriate amount of water to the mixture and stir for 10 minutes; Pour the mixed green sand into the mold and compact it by vibration to form a cavity of the desired shape; Adjust the vibration table according to the vibration parameter threshold; The prepared cavity is naturally dried or low-temperature dried to obtain the final green sand mold.

2. The method for producing micro-segment green sand for ultrafine grinding according to claim 1, characterized in that: The mixing of bentonite, coal powder and old sand in a certain proportion includes: Select high-quality bentonite and coal powder with moderate fineness as reducing agent and fuel. At the same time, the selected old sand needs to be screened and cleaned to remove impurities and dust; The preparation ratio of bentonite, coal powder and old sand is 1:1:8; Weigh bentonite, coal powder and old sand according to the above proportions, put them into a mixer, start the mixer and carry out preliminary mixing.

3. The method for producing micro-segment green sand for ultrafine grinding according to claim 1, characterized in that: The step of adding an appropriate amount of water to the mixture and stirring and mixing for 10 minutes includes: The amount of water added is 5% to 10% of the total weight of the mixture, and the expression is as follows: Where W is the amount of water added, in kg, P is the percentage of water, ranging from 5% to 10%, and M is the total weight of the mixture, in kg; Spray the calculated water evenly into the mixture, then turn on the mixer and stir and mix for 10 minutes; During the mixing process, make sure the mixture is fully moistened and free of dry lumps and lumps.

4. The method for producing micro-segment green sand for ultrafine grinding according to claim 1, characterized in that: The mixed green sand is poured into the mold and compacted by vibration to form a cavity of a desired shape, including: Choose a mold of appropriate size and shape, ensure that the inner surface of the mold is smooth, free of burrs and cracks, and treat the inner surface of the mold with a release agent; Pour the mixed green sand evenly into the mold; During the filling process, vibrate the mold appropriately to allow the green sand to be filled into the mold more tightly; Place the mold filled with green sand on a vibration table and start the vibration table for vibration compaction.

5. The method for producing micro-segment green sand for ultrafine grinding according to claim 4, characterized in that: During the vibration compaction process, the vibration frequency and amplitude need to be optimized and designed, and the expressions are as follows: Where v is the vibration frequency in Hz, A is the vibration amplitude in mm, t is the vibration time in seconds, indicating the duration of the vibration, and k is the material constant in N·s 2 / mm 3 .

6. The method for producing micro-segment green sand for ultrafine grinding according to claim 1, characterized in that: The adjusting of the vibration table according to the vibration parameter threshold value includes: When the value of f(v,A,t) is between L1 and L2, it means that the vibration parameters are set reasonably; When the value of f(v,A,t) is less than L1, it means that the vibration parameters are too weak, the compaction effect of green sand is poor, and there may be voids and bubbles. At this time, the vibration frequency v or vibration amplitude A should be increased, or the vibration time t should be extended; When the value of f(v,A,t) is greater than L2, it means that the vibration parameters are too strong, which may cause excessive compaction of the green sand and affect the dimensional accuracy and surface quality of the cavity. At this time, the vibration frequency v or vibration amplitude A should be reduced, or the vibration time t should be shortened.

7. The method for producing micro-segment green sand for ultrafine grinding according to claim 1, characterized in that: The step of drying the mold cavity naturally or at low temperature to obtain the final green sand mold includes: Place the finished cavity in a well-ventilated environment to dry naturally for 24 hours; Or put the prepared cavity into an oven, set the temperature to 100°C to 150°C, and dry it for 2 to 4 hours.